DOSIS DAN WAKTU APLIKASI PUPUK DOLOMIT (CaMg(CO3)2) SERTA PENGARUHNYA TERHADAP CEMARAN GETAH KUNING BUAH MANGGIS (Garcinia mangostana L.) - Rohmani Astuti (CROP AGRO, Scientific Journal of Agronomy, 2020)
Yellow sap contamination is one of the constraints in producing export quality of mangosteen. The contamination can be reduced by strengthening cell walls with an application of Ca during the fruit growth stage. This study aimed to explore dosages and application times of dolomite (CaMg(CO3)2) and their effects on yellow sap contamination. The experimental design was a Randomized Block Design with two factors and the factors were arranged factorially with three replications. The first factor was dosage of dolomite (D) that consisted of 0 g/tree, 3000 g/tree, and 9000 g/tree, and the second factor was time of dolomite application that consisted of 2 weeks after anthesis (WAA) and 6 WAA. The results showed that the application of dolomite at 3000 g/tree and 9000 g/tree reduced the percentage of yellow sap contamination in fruit by 23,07% and 24,20%, repectively as compared to no dolomite application treatment. Meanwhile, time of application did not affect yellow sap contamination in fruit. It is suggested to apply 3000 g/tree of dolomite at the fruit growth stage to reduce yellow sap contamination in mangosteen fruit.